Healing Heels: A Meta-analysis of Platelet-rich Plasma vs Corticosteroid Injections in Plantar Fasciitis Treatment - Clevio Desouza; Vijay Shetty (Journal of Foot and Ankle Surgery (Asia Pacific))
Introduction: Plantar fasciitis (PF) is a common cause of heel pain, particularly affecting individuals involved in running sports and those with prolonged standing activities. While various nonoperative treatments are available, there is no consensus on the optimal therapy. Corticosteroid injections offer short-term relief but have associated risks and limited long-term efficacy. Platelet-rich plasma (PRP) has emerged as a potential alternative, with conflicting evidence regarding its effectiveness compared to corticosteroids. Materials and methods: This systematic review and meta-analysis adhered to Cochrane and PRISMA guidelines. We included level 1 and level 2 studies from 2015 to 2023 that compared intralesional corticosteroid and PRP injections for treating PF with at least 6 months of follow-up. Comprehensive searches were conducted in Medline, Embase, Scopus, and Google Scholar. Data extraction and quality assessment were independently performed by two reviewers, using the Cochrane risk of bias tool. Statistical analyses, including heterogeneity and subgroup analyses, were conducted using Review Manager 5.3. Results: From 826 initial studies, 13 met inclusion criteria, encompassing 941 patients (PRP 476, corticosteroids 465). Platelet-rich plasma demonstrated no significant pain relief over corticosteroids at 3 months [standard mean difference (SMD) = −0.37; 95% confidence interval (95% CI) = −1.15 to 0.41; I² = 96%; p = 0.35]. However, PRP showed statistically significant improvements in VAS scores at 6 months (SMD = −1.92; 95% CI = −3.33 to −0.51; I² = 98%; p = 0.008) and 1 year (SMD = −0.37; 95% CI = −0.70 to −0.03; I² = 0%; p = 0.03). For function, PRP resulted in significant improvements in American Orthopaedic Foot & Ankle Society (AOFAS) scores at 6 months (SMD = 0.89; 95% CI = 0.09 to 1.69; I² = 94%; p = 0.03) but not at 3 months (SMD = −0.09; 95% CI = −0.63 to 0.44; I² = 86%; p = 0.73) or 1 year (SMD = 1.68; 95% CI = −0.09 to 3.45; I² = 96%; p = 0.06). Conclusion: Platelet-rich plasma is more effective than corticosteroid injections for pain control from 6 months to 1 year. In the short term, PRP offers no significant advantage. Interpretation of these findings should consider the quality of studies, risk of bias, and variability in PRP preparation protocols, which affect the internal and external validity. Thus, compelling evidence for PRP's superiority in PF treatment remains elusive.